2017
DOI: 10.1007/s00259-017-3808-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantification: there is more to worry about than good scanner hardware and reliable calibration

Abstract: Positron emission tomography (PET) is Ban analytical imaging technology developed to use compounds labelled with positron-emitting radioisotopes as molecular probes to image and measure biochemical processes of mammalian biology in vivo^ [1]. One outstanding feature of the PET technology is the ability to perform absolute quantification of regional perfusion, metabolism, and function [2]. There are clinical demands for quantification regarding description of biodistribution, dosimetry, intra-and inter-individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The same study revealed that the maximum standardized uptake value (SUV max ) of lesions attributed to benign origin was higher for 18 F-PSMA-1007-PET than for 68 Ga-PSMA-11-PET [ 2 ]. These differences between PET scans of different radionuclides might be caused by a combination of different effects: Radiotracers differ in their biokinetics and affinities [ 5 ]. In addition, state-of-the-art digital PET/CT scanners allow PET measurements with higher sensitivity and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The same study revealed that the maximum standardized uptake value (SUV max ) of lesions attributed to benign origin was higher for 18 F-PSMA-1007-PET than for 68 Ga-PSMA-11-PET [ 2 ]. These differences between PET scans of different radionuclides might be caused by a combination of different effects: Radiotracers differ in their biokinetics and affinities [ 5 ]. In addition, state-of-the-art digital PET/CT scanners allow PET measurements with higher sensitivity and spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…lesions attributed to benign origin was higher for 18 F-PSMA-1007-PET compared to 68 Ga-PSMA-11-PET (2). It is currently unclear whether these differences are due to different biokinetics and a nities of the tracers (5), different counting statistics in the respective measurements or whether different physical properties increase detection probability. The maximum positron energy and thus the mean range in tissue differ between 18 F and 68 Ga: positrons arising from the decay of 68 Ga feature a three times higher endpoint energy than that of 18 F and therefore have a much greater mean range in tissue (3.5 mm compared to 0.6 mm) (Table 1).…”
mentioning
confidence: 99%